“Emotion or logic?: Utilization of Dilemma and Gamification in the Teaching of 3rd Junior High School Literature (London Journal of Research In Humanities and Social Sciences, 2024)
Dilemma-based learning (DBL) and Gamification are two educational techniques that, have received the attention of both educational theorists and the educational community in general in recent years. The purpose of this article is to present a didactic scenario for the teaching of the 3rd Junior High School Literature course entitled “With emotion or logic?”. This scenario was designed and implemented within the Erasmus+ program “Gamified Introduction to Gamification”. The innovation of the scenario lies in its student-centered nature and, above all, in the utilization of the principles of Dilemma-based learning and Gamification. The students, acting within a framework of collaborative activities, both digital and non-digital, managed to approach the objectives of the scenario to a very satisfactory degree.
Keywords: discourse markers; shell noun; causal relation; Problem-Solution; clause-relational approach; Mobility; Southwestern Europe; Struma River Valley; Neolithization; Early Neolithic; Dilemma-based learning; Gamification; 3rd Junior High School Literature.